The synergistic effect of Zeolites type (?) with chlorinated rubber as flame retardants for unsaturated polyester resin (Baghdad Science Journal, 2025)
In this work, the synergistic effect of chlorinated rubber (additive I),with zeolite 3A (additive II), zeolite 4A (additive III), and zeolite 5A (additive IV) in (1:1) weight percentage, on the flammability for unsaturated polyester resin was studied in the weight ratios for (3,7,10,13&15%) by preparing films of (130×130×3) mm in diameters. Three standard test methods used to measure were the flame retardation which are; ASTM: D-2863, ASTM: D- 635& ASTM: D-3014. Results obtained from these tests indicated that all of the additives were effective additive IV has the highest efficiency as a flame retardant.